2011
DOI: 10.1128/cvi.05041-11
|View full text |Cite
|
Sign up to set email alerts
|

Novel Epitopic Region of Glucosyltransferase B from Streptococcus mutans

Abstract: In the development of a component vaccine against caries, the catalytic region (CAT) and glucan-binding domain (GBD) of glucosyltransferase B (GtfB) from Streptococcus mutans have been employed as target antigens. These regions were adopted as primary targets because they theoretically include epitopes associated with enzyme function. However, their antigenicities have not been fully evaluated. Although there are many reports about successful vaccination using these components, the principle has not yet been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…For example, novel epitopes of S. mutants have been studied for years. 24,25,26 Our current studies focus on developing highly efficacious vaccines through the identification of the most immunogenic T and B cells epitopes. The synthesis of platforms bearing both peptide epitopes and a lipophilic moiety is now considered a valuable way to produce self-adjuvanting constructs that allow overcoming intrinsic low peptide immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, novel epitopes of S. mutants have been studied for years. 24,25,26 Our current studies focus on developing highly efficacious vaccines through the identification of the most immunogenic T and B cells epitopes. The synthesis of platforms bearing both peptide epitopes and a lipophilic moiety is now considered a valuable way to produce self-adjuvanting constructs that allow overcoming intrinsic low peptide immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…These regions have been selected because, in theory, they include epitopes associated with its enzymatic function. [40] found that the variable region (VR) at the N-terminal of GtfB is specific to S. mutans and is not conserved among other streptococcal Gtfs, being a promising epitope for the development of an effective vaccine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…RISKESDAS stated that, in 2007, caries prevalence in Indonesia is 46.5% [7]. There have been various eff orts that were attempted in preventing carries, including through active and passive immunization [8][9][10][11][12][13]. Recently, passive immunization and anti-microbial substances are the two things that are mostly utilized for the development of caries vaccines [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%